Paddle‐based rotating‐shield brachytherapy. Issue 10 (23rd September 2015) - Liu, Yunlong; Flynn, Ryan T.; Kim, Yusung; Dadkhah, Hossein; Bhatia, Sudershan K.; Buatti, John M.; Xu, Weiyu; Wu, Xiaodong
Abstract : Purpose: The authors present a novel paddle‐based rotating‐shield brachytherapy (P‐RSBT) method, whose radiation‐attenuating shields are formed with a multileaf collimator (MLC), consisting of retractable paddles, to achieve intensity modulation in high‐dose‐rate brachytherapy. Methods: Five cervical cancer patients using an intrauterine tandem applicator were considered to assess the potential benefit of the P‐RSBT method. The P‐RSBT source used was a 50 kV electronic brachytherapy source (Xoft Axxent™). The paddles can be retracted independently to form multiple emission windows around the source for radiation delivery. The MLC was assumed to be rotatable. P‐RSBT treatment plans were generated using the asymmetric dose–volume optimization with smoothness control method [Liu et al., Med. Phys.41 (11), 111709 (11pp.) (2014)] with a delivery time constraint, different paddle sizes, and different rotation strides. The number of treatment fractions (fx) was assumed to be five. As brachytherapy is delivered as a boost for cervical cancer, the dose distribution for each case includes the dose from external beam radiotherapy as well, which is 45 Gy in 25 fx. The high‐risk clinical target volume (HR‐CTV) doses were escalated until the minimum dose to the hottest 2 cm 3 ( D 2cm 3 ) of either the rectum, sigmoid colon, or bladder reached their tolerance doses of 75, 75, and 90 Gy3, respectively, expressed as equivalent doses in 2 Gy fractions (EQD2 with α / β = 3 Gy). Results: P‐RSBT outperformed the two other RSBT delivery techniques, single‐shield RSBT (S‐RSBT) and dynamic‐shield RSBT (D‐RSBT), with a properly selected paddle size. If the paddle size was angled at 60°, the average D 90 increases for the delivery plans by P‐RSBT on the five cases, compared to S‐RSBT, were 2.2, 8.3, 12.6, 11.9, and 9.1 Gy10, respectively, with delivery times of 10, 15, 20, 25, and 30 min/fx. The increases in HR‐CTV D 90, compared to D‐RSBT, were 16.6, 12.9, 7.2, 3.7, and 1.7 Gy10, respectively. P‐RSBT HR‐CTV D 90 ‐values were insensitive to the paddle size for paddles angled at less than 60°. Increasing the paddle angle from 5° to 60° resulted in only a 0.6 Gy10 decrease in HR‐CTV D 90 on average for five cases when the delivery times were set to 15 min/fx. The HR‐CTV D 90 decreased to 2.5 and 11.9 Gy10 with paddle angles of 90° and 120°, respectively. Conclusions: P‐RSBT produces treatment plans that are dosimetrically and temporally superior to those of S‐RSBT and D‐RSBT, although P‐RSBT systems may be more mechanically challenging to develop than S‐RSBT or D‐RSBT. A P‐RSBT implementation with 4–6 shield paddles would be sufficient to outperform S‐RSBT and D‐RSBT if delivery times are constrained to less than 15 min/fx.